Asymptomatic Isolated Cervical Tubercular Lymphadenopathy, How to Proceed?: A Case Series - Ravi Singh Dogra; Arjun Singh; Vinay Bhardwaj; Poonam; Srijan Pandey; Gunjan Modgil; Arpit Goel (Asian Journal of Medical Research, 2020)
Tuberculosis is a highly prevalent disease in developing countries, the majority of cases are pulmonary and rest are extra-pulmonary. Cervical LN tuberculosis is one of the most common types of extra-pulmonary tuberculosis. Isolated cervical tubercular Lymphadenitis without accompanying pulmonary tuberculosis or another form of tuberculosis in the body is rare and, when present, requires thorough clinical examination and investigation. In the investigation of such patients, FNAC plays a major role, and aspirate should be tested for AFB through ZN stain and CBNAAT (PCR). Cervical tubercular Lymphadenitis is mainly a disease of young with a female predominance. All patients of cervical tubercular Lymphadenitis must receive antitubercular therapy with strict follow up for compliance and possible side effects from treatment.